PEMBERDAYAAN SULAM ANGKINAN MELALUI STRATEGI BRANDING DAN JURNALISME DIGITAL BERBASIS MEDIA SOSIAL - Suhendra; Arif Ardiansyah; Siti Lady Havivi; Budi Santoso; Anton Yusuf (LPPM UNINUS, 2025)
Abstract This community engagement program aims to empower Sulam Angkinan artisans in Kampung Sunan, Sungai Lais, Palembang, through branding enhancement and digital journalism strategies on social media. Using a qualitative-descriptive approach, the activities consisted of participatory workshops and direct mentoring in content production for Instagram and TikTok. The program resulted in improved visual branding awareness, digital storytelling skills, and stronger online exposure, allowing artisans to present cultural identity and promote products more effectively. This empowerment model demonstrates that integrating local heritage with digital culture can increase visibility and create economic sustainability for small-scale artisans. Keywords: Angkinan embroidery; branding; community empowerment; digital journalism; Instagram marketing.